Soil N, P, and C dynamics of upland and seasonally flooded forests of the Brazilian Pantanal - Pinto, O.B. (2020)
Seasonal variations in cerrado nutrient availability and mineralization are poorly understood, especially for “hyperseasonal” cerrado, which experiences both flooding and drought over an annual cycle. Here we quantified seasonal variations in soil ammonium (NH4+), phosphorus (P), and organic C (SOC) concentration and net mineralization in upland and seasonally flooded cerrado forests of the Brazilian Pantanal, and hypothesized that NH4+, P, and SOC concentrations and net mineralization would decline under flooding and increase during the dry season as soil becomes unsaturated. Thus, despite the large seasonal and spatial variations in hydrology, the effects of flooding depended on the particular response variable studied and the season.